Analisis Pemanfaatan Media Audio-Visual dan Dampaknya Terhadap Minat Belajar Siswa di SDN 110 Lura - Aliya Asy’arie; Asmah Amir; A. Suharman (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
Learning media is essential to increase student interest and learning effectiveness. Interactive and technology-based learning, such as digital apps, videos and animations, can make the classroom dynamic and fun. This attracts students' attention and encourages them to actively participate in the learning process. According to research, effective use of learning media in the education curriculum can significantly increase students' interest in learning. This research uses descriptive qualitative research which means looking at the process of events before coming to a conclusion and aims to describe and understand the phenomenon being studied. Data is collected through documentation, interviews and direct observation or observation, this research also collects information through analyzing existing literature to gain a more comprehensive understanding of the phenomenon being discussed. The utilization of audio-visual media in educational technology is an important breakthrough that can increase elementary school students' interest in learning. It offers a combination of visual and audio elements that can attract students' attention more effectively than traditional methods such as textbooks or lectures. The utilization of audio-visual media in educational technology shows significant potential for primary school students to increase their interest in learning. By presenting subject matter through images, videos and sound, the learning process becomes more interesting and interactive, which helps to reduce student boredom and increase their engagement in the classroom.